Tourism--passport to development? : Perspectives on the social and cultural effects of tourism in developing countries ([New York] Published for the World Bank and Unesco [by] Oxford University Press, 1979)
Tourism, spurred by jumbo jets, charter tours, and the affluence of the industrial nations, has become a major economic activity. To many developing countries with few resources other than sunny climates, sandy beaches, and exotic cultures, it has see med to offer an opportunity to secure foreign exchange and stimulate economic growth. Critics question, however, whether tourism yields economic returns commensurate with its costs and express concern about its possibly adverse social and cultural effects.
Includes bibliographical references and index.
ISBN 0-19-520150-7 Pbk : -2.50.
Keywords: Tourism -- Congresses; Tourisme -- Congr?es.; Toerisme; Developing countries -- Social conditions -- Effects of international tourism, 1970-1979